Satu Sejarah Pendidikan Masyarakat Bidayuh di Sarawak Sebelum Tahun 1963 - Angelina Ansley; Bilcher Bala (2018)
Bidayuh is one of the minority ethnic groups in Malaysia. In Sarawak, Bidayuh is the fourth largest ethnic group after Iban, Chinese and Malay. The spreading of Christian faith to the villages of Bidayuh was simultaneous with the development of formal education. However, not all the Bidayuh people have the opportunity to receive formal education. This study found that the failure to implement formal education before independence was due to the existence of certain obstacles to the Bidayuh people, the mission group and the government policy. This article will describe in depth the history and challenges in education among the Bidayuh before independence based on information from primary, secondary and oral sources. This study is important because it revealed the history of education among the Bidayuh people before independence.